Optimization of gaseous nitriding of carbon iron-based alloy based on fatigue resistance modelling. (May 2018) - Weil, H.; Barrallier, L.; Jégou, S.; Caldeira-Meulnotte, N.; Beck, G.
Highlights: Calculation of lifetime with the influence of residual stresses and hardness. Optimization of the nitriding parameters with a reverse method. Calculation of hardness and residual stresses induced by gaseous nitriding process. Comparison of calculated fatigue limits with tests in rotational bending. Abstract: Gaseous nitriding of steels is a well-established thermochemical surface treatments that increases the fatigue resistance of treated parts. The present work proposes a modelling of the fatigue life as a function of the applied stress. It takes into account the hardness and compressive residual stresses that developed during nitriding. The model is suitable to help optimizing nitriding parameters by reverse modelling.